Peranan Humas dalam Sosialisasi Fungsi dan Tugas Lembaga Tinggi Negara DPD RI : Studi Kasus Sosialisasi Peluncuran Tagline “Dari Daerah untuk Indonesia” pada HUT DPD RI Ke-16 - Kristiyanto, Mas Aryo; Sunarto, Sunarto; Damayanti, Novita (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the role of public relations in the socialization of the functions and duties of the high state institution, DPD RI, and to identify the obstacles faced by public relations in this process. This research also examines the use of media and facilities for socializing the tagline